Clinical manifestations of syphilis in the oral cavity — a review - Villar Medeiros, Ana Beatriz; Silva, Renivânia Pereira da; Oliveira, Francimária Aparecida da Silva; Fontes de Morais, Letícia Amanda; Guerra Neto, Custódio Leopoldino de Brito; Oliveira Guerra, Ângelo Roncalli; Medeiros, Andryele Eduarda de Araújo; Araújo, Maria Heloyze Medeiros de; Pereira, Larissa de Alcântara (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Syphilis is a sexually transmitted infection caused by Treponema pallidum bacterium, which impact on a significant increase in contagions reported worldwide, bringing up the need of urgent actions to ensure the control, treatment, and diagnosis of the disease. Objective: Given this context, this work presents a bibliographical review on syphilis, aiming to describe the most common oral manifestations that occur on the four stages of this infection. Methods: For the literature review, the searches were carried out in the PubMed, Science Direct, Scientific Electronic Library Online, Latin American and Caribbean Health Sciences Literature and databases of Virtual Health Library. Results: Regarding the primary syphilis, the main clinical manifestations in the oral cavity include chancres in the palate, buccal mucosa, tongue, and lips. In the secondary stage, the presence of diffuse and nonspecific oral lesions was identified. In tertiary syphilis, stomatitis and glossitis are present, being the hard palate and the tongue the main affected regions. In congenital syphilis, the patients are affected with dental and jaw malformations. Conclusion: The clinical manifestations of syphilis in the oral cavity can appear at any stage of the infection, being the oral cavity the second most affected region by this sexually transmitted infection. Therefore, the knowledge regarding this subject is extremely important for health professionals, as well as for the population, being essential to carry out the correct diagnosis and adequate treatment for the rapid cure of this infection.